Evaluation of Gamma-Rays Attenuation Properties of Vanadium-Doped Alloys - Ravangvong, Sunantasak (Indochina Applied Sciences, 2020)
In this work, the gamma ray shielding properties of vanadium doped alloys have been evaluated. The values of mass attenuation coefficients (mm), effective atomic numbers (Zeff), effective electron densities (Nel), mean free path (MFP) and half value layers (HVL) were computed by WinXCom software program at photon energy range 1 keV – 100 GeV. The values of mm, Zeff and Nel were decreased with an increasing in V content whereas MFP and HVL were increased with an increasing in V content. It was extrapolated that the increasing in the composition of vanadium in alloys system which vanadium to decrease in the gamma ray shielding properties of alloys system.